Complex Ownership Structures and Corporate Valuations - Laeven, Luc.; Levine, Ross. (Washington, D.C. : International Monetary Fund, 2007)
The bulk of corporate governance theory examines the agency problems that arise from two extreme ownership structures: 100 percent small shareholders or one large, controlling owner combined with small shareholders. In this paper, we question the empirical validity of this dichotomy. In fact, one-third of publicly listed firms in Europe have multiple large owners, and the market value of firms with multiple blockholders differs from firms with a single large owner and from widely-held firms. Moreover, the relationship between corporate valuations and the distribution of cash-flow rights across multiple large owners is consistent with the predictions of recent theoretical models.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet